Assessing Employee Loyalty through Organizational Attributes in Telecom Sector: An Empirical Evidence - Tariq, Haleema; Ilyas, Muhammad; Abdul Rehman, Chaudhary (Advances in Social Sciences Research Journal, 2017)
Employee loyalty is a value addition concept in the overall organizational success. The main purpose of this research study is to identify the impact of core attributes of organizations on employee loyalty and their predictability power for the concept particularly in telecommunication sector in Pakistan. This is a correlational study conducted to investigate the relationships. Data were collected using a survey questionnaire validated under a pilot study. Initially 250 questionnaires were distributed among employees and valid responses of 190 questionnaires were analysed. Found that job involvement, perceived organizational support, employee engagement and distributive justice have positively significant impact on employee loyalty. Due consideration is required for the factors like distributive justice and perceived organizational support to focus on more amicable work environment and promote the supportive mechanisms for employees to work and excel. The main predictors of employee loyalty connote a healthy working environment reflecting the organizational efforts for creating a social impact. Employees would gain special attention in terms of the factors being addressed in this study. The research focuses on the growing importance and demand for crystallizing the concept of employee loyalty.